La parola oggettivata - Olivieri, Fabio (Rivista Italiana di Filosofia del Linguaggio, 2009)
In contemporary society words tend to lose their main daty: naming the objects around us. They become meaningless empty containers that end up to be incorporated by their referents. The desire to oversimplify every conversation comes to defraud it of its consistency, an attitude that involves a distortion of language and reality. After a brief introduction about etymological origin of the word, in this article, I’m going to address some linguistics Chomsky’s contributions and cultural psychology of Bruner, focusing on some experiments conducted as part of psycholinguistics to demonstrate how the perception of reality is influenced by the use of a particular language. Emphasizing the importance of three main factors of communication (talker, listener and context) I’m going to talk about different ways to analyse an enunciated, recognizing to the words the ability to build worlds and to attribute meanings to the life. I’m finally going to deepen some terms of common use in order to show as their distortion induces the subject to deprive of their same substance these terms respect to their listeners.